2023
DOI: 10.1021/acs.energyfuels.3c02099
|View full text |Cite
|
Sign up to set email alerts
|

Optimized High-Efficiency Solar Cells with Dual Hybrid Halide Perovskite Absorber Layers

Sagar Bhattarai,
Deepthi Jayan K,
Rahul Pandey
et al.

Abstract: The single, double absorbers-based perovskite solar cells (PSCs) have attracted considerable attention of researchers in the past few years due to their promising photovoltaic parameters. The present work discusses a comparative performance analysis of the two configurations, namely the ITO/C60/MAPb­(I1–x Cl x )3/CuSCN/Au, ITO/C60/MAPbI3/CuSCN/Au, and ITO/C60/MAPb­(I1–x Cl x )3/MAPbI3/CuSCN/Au composed of a single layer of perovskite as the absorber and a double layer of two different halide perovskites as abs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 67 publications
0
4
0
Order By: Relevance
“…In the quest for enhanced efficiency and thermal stability in perovskite solar cells, this study delves into simulations comparing the performance of these cells with and without interface layers, elucidating the implications of temperature on each parameter. Temperature has a notable influence on how well solar cells function 11 , 72 . Most PV cells achieve their highest efficiency when operating at around room temperature, which is about 300 K. To study how temperature affects the performance of PSC, the temperature varied across the range of 300–450 K for all the structures and the results are presented in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In the quest for enhanced efficiency and thermal stability in perovskite solar cells, this study delves into simulations comparing the performance of these cells with and without interface layers, elucidating the implications of temperature on each parameter. Temperature has a notable influence on how well solar cells function 11 , 72 . Most PV cells achieve their highest efficiency when operating at around room temperature, which is about 300 K. To study how temperature affects the performance of PSC, the temperature varied across the range of 300–450 K for all the structures and the results are presented in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…As expected, due to the previously discussed reasons, the optimized NC45 design not only offered saturated absorption for saturation region, but also retained the uncompromised performance for size-dependent region. Unlike the previous computational studies where majority of the attention was draw on examining new types of PTF materials and defect density’s impact on the PV figure of merits of the device 26 31 , our work focuses more on the unique optical properties of PTF’s NC based nanostructures and exploring its PCE enhancement potential.…”
Section: Resultsmentioning
confidence: 99%
“…Optically, this structure provides a smooth change in the effective refractive index facing the light incident direction, which would also be an added benefit to light trapping performance by reflection suppression 25 . Furthermore, several computational studies had successfully revealed great potential of various kinds of PTF SCs on their high performing PCEs 26 31 .…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, lead halide perovskite materials with the structure ABX 3 (where A is caesium, B is a lead cation and X is a halide anion) exhibit numerous advantages such as high brightness, and high photoluminescence quantum yield (PLQY) with narrow size distribution, which can provide great potential in optoelectronic devices [1]. These lead halide perovskite-based various applications such as solar cells [2][3][4][5][6][7][8][9], photodetectors [10], light-emitting diodes (LEDs) [11][12][13][14][15][16][17] and low-threshold lasers [18][19][20], etc., have been increasingly investigated. Although they have excellent optical properties, the lead halide perovskite materials' sensitive surface chemistry with moisture, oxygen in the ambient environment, and organic polar solvents are still one of the major issues.…”
Section: Introductionmentioning
confidence: 99%